Behavioral Economic Strategies Increase Adverse Event Reporting in Pediatric Anesthesia - Guan TK; Willer BL; Stevens J; Tobias JD; Olbrecht VA (ClinicoEconomics and Outcomes Research, 2024)
Tiffany K Guan,1 Brittany L Willer,2,3 Jack Stevens,4,5 Joseph D Tobias,2,3 Vanessa A Olbrecht2,3 1College of Medicine, The Ohio State University, Columbus, OH, USA; 2Department of Anesthesiology & Pain Medicine, Nationwide Children’s Hospital, Columbus, OH, USA; 3Department of Anesthesiology & Pain Medicine, The Ohio State University Wexner Medical Center, Columbus, OH, USA; 4Department of Pediatrics, Nationwide Children’s Hospital and The Ohio State University, Columbus, OH, USA; 5Center for Clinical Excellence, Nationwide Children’s Hospital, Columbus, OH, USACorrespondence: Brittany L Willer, Nationwide Children’s Hospital, 700 Children’s Drive, Columbus, Ohio, 43205, USA, Email Brittany.Willer@nationwidechildrens.orgIntroduction: Identification and reporting of severe adverse events (SAEs) during anesthesia care remains critical in identifying areas of improvement in perioperative patient care. Although many healthcare organizations rely on the self-reporting of SAEs, under-reporting may limit the identification of the true incidence of these events. To circumvent these barriers, many healthcare systems leverage the Electronic Medical Record (EMR) by incorporating an Anesthesia Information Management System (AIMS).Methods: We followed the Institute for Healthcare Improvement’s Model of Improvement and implemented behavioral economic-based interventions to our perioperative practice including adding a deliberation-promoting “hard stop” that required the anesthesiologists to report the occurrence or absence of a “notable event” prior to closing a patient’s encounter in the EMR system.Results: At baseline, 53% of SAEs were self-reported. The interventions resulted in a baseline shift to more than 75% self-reporting, a relative increase of 42%.Conclusion: An increase in reporting of SAEs was achieved with simple interventions including modifications of the EMR which were done with limited financial impact or interruption in the work flow.Keywords: adverse events, pediatric anesthesia, intraoperative care, quality and safety